SPATIAL EVALUATION OF AMBON CITY SPATIAL PLAN FROM FLOOD VULNERABILITY ASPECT - Anelia Wlary; Suhadi Purwantara; Nurul Khotimah; Heinrich Rakuasa (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2026)
Flooding is a common disaster in Indonesia, including Ambon City. This study evaluates the 2011-2031 Ambon City Spatial Plan (RTRW) with a focus on flood vulnerability using the Multi-Criteria Analysis (MCA) method. Six crucial parameters, such as landform, elevation, land use, river buffers, soil type, and rainfall, were analyzed. The results show that Flood Hazard areas are dominated by low (22,461 ha), medium (9,872 ha), and high (1,833 ha) classes. Crucial findings indicate that 50.08% of settlements (2,222 ha) are in the high hazard class and 49.91% (2,214 ha) are in the medium class. The most vulnerable spatial pattern is medium-density settlements. Therefore, strategic recommendations include strengthening drainage infrastructure, implementing strict zoning for new developments, and increasing community participation in spatial planning. These steps are expected to increase the city's resilience to flooding and support environmental sustainability. Keywords: Flood Vulnerability, Spatial Evaluation, Urban Spatial Planning